Bovine Lactoferrin Suppresses Tumor Angiogenesis through NF-κB Pathway Inhibition by Binding to TRAF6 - Nurina Febriyanti Ayuningtyas; Chanbora Chea; Toshinori Ando; Karina Erda Saninggar; Keiji Tanimoto; Toshihiro Inubushi; Nako Maishi; Kyoko Hida; Masanobu Shindoh; Mutsumi Miyauchi; Takashi Takata (MDPI AG, 2023)
Tumor angiogenesis is essential for tumor progression. The inhibition of tumor angiogenesis is a promising therapy for tumors. Bovine lactoferrin (bLF) has been reported as an anti-tumor agent. However, bLF effects on tumor angiogenesis are not well demonstrated. This study evaluated the inhibitory effects of bLF on tumor angiogenesis in vivo and in vitro. Herein, tumor endothelial cells (TECs) and normal endothelial cells (NECs) were used. Proliferation, migration, tube formation assays, RT-PCR, flow cytometry, Western blotting, siRNA experiments and immunoprecipitation were conducted to clarify the mechanisms of bLF-induced effects. CD-31 immunoexpression was examined in tumor tissues of oral squamous cell carcinoma mouse models with or without Liposomal bLF (LbLF)-administration. We confirmed that bLF inhibited proliferation/migration/tube formation and increased apoptosis in TECs but not NECs. TNF receptor-associated factor 6 (TRAF6), p-p65, hypoxia inducible factor-α (HIF-1α) and vascular endothelial growth factor (VEGF) were highly expressed in TECs. In TECs, bLF markedly downregulated VEGF-A, VEGF receptor (VEGFR) and HIF-1α via the inhibition of p-p65 through binding with TRAF6. Since NECs slightly expressed p-p65, bLF-TRAF-6 binding could not induce detectable changes. Moreover, orally administrated LbLF decreased CD31-positive microvascular density only in TECs. Hence, bLF specifically suppressed tumor angiogenesis through p-p65 inhibition by binding to TRAF6 and suppressing HIF-1α activation followed by VEGF/VEGFR down-regulation. Collectively, bLF can be an anti-angiogenic agent for tumors.